2016
DOI: 10.1038/tp.2015.200
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation and high entropy of neonatal experience predict adolescent emotional outcome

Abstract: Vulnerability to emotional disorders including depression derives from interactions between genes and environment, especially during sensitive developmental periods. Across evolution, maternal care is a key source of environmental sensory signals to the developing brain, and a vast body of work has linked quantitative and qualitative aspects of maternal care to emotional outcome in children and animals. However, the fundamental properties of maternal signals, that promote advantageous vs pathological outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
260
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(297 citation statements)
references
References 68 publications
34
260
2
1
Order By: Relevance
“…This inconsistency in maternal behavior introduces instability to an otherwise extremely stereotyped behavioral repertoire, altering the expected and required pattern of sensory stimulation received by the infant during a critical period of development. Inconsistency in maternal behavior has been previously observed using a more extreme early-life adversity model where the mother and litter are housed in a cage with a mesh bottom and provided with a single paper towel for nest building (Ivy et al, 2008; Molet et al, 2016). Importantly, the combination of increased negative maternal behavior, altered nursing behaviors, and inconsistent maternal behavior indicates that changes in maternal care were not limited to reductions in quantity and quality, but also to increased inconsistency in the pattern of care received from the caregiver in response to the insufficient bedding environment.…”
Section: Discussionmentioning
confidence: 80%
“…This inconsistency in maternal behavior introduces instability to an otherwise extremely stereotyped behavioral repertoire, altering the expected and required pattern of sensory stimulation received by the infant during a critical period of development. Inconsistency in maternal behavior has been previously observed using a more extreme early-life adversity model where the mother and litter are housed in a cage with a mesh bottom and provided with a single paper towel for nest building (Ivy et al, 2008; Molet et al, 2016). Importantly, the combination of increased negative maternal behavior, altered nursing behaviors, and inconsistent maternal behavior indicates that changes in maternal care were not limited to reductions in quantity and quality, but also to increased inconsistency in the pattern of care received from the caregiver in response to the insufficient bedding environment.…”
Section: Discussionmentioning
confidence: 80%
“…For each assay (corticosterone, neurodevelopment, gene expression, and behavior), we took care to insure that animals from a minimum of two separate litters were sampled from. In previous studies of both mice and rats, elegant studies find that this manipulation leads to a fragmentation in maternal care and elevations in stress hormones in the dam (Molet et al, 2016; Rice et al, 2008; and Avishai-Eliner et al, 2001). Specifically, in those reports, the authors observed an increase in the number of departures from the nest by the dam, but no change in licking and grooming or arched back nursing (Molet et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies of both mice and rats, elegant studies find that this manipulation leads to a fragmentation in maternal care and elevations in stress hormones in the dam (Molet et al, 2016; Rice et al, 2008; and Avishai-Eliner et al, 2001). Specifically, in those reports, the authors observed an increase in the number of departures from the nest by the dam, but no change in licking and grooming or arched back nursing (Molet et al, 2016). As maternal behavior is difficult to assess mice, in part due to their small size and lack of stereotyped nursing posture, we did not carry out detailed assessment of maternal behavior, and instead relied on our successful replication of other core features of this paradigm, which includes growth restriction of litters.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, there is little evidence of physical stress of the pups, with no hypothermia and minimal weight changes . Thus, the early-life stress that is engendered seems to be a direct result of the fragmented, unpredictable sensory signals from the mothers (Moriceau et al 2009;Baram et al, 2012;Molet et al, 2014Molet et al, , 2015a. These seem to provoke chronic early-life stress, including persistent elevation of plasma corticosterone and adrenal hypertrophy (Gilles et al, 1996;Rice et al, 2008).…”
Section: What Generates Stress Early In Life? Are the Consequences A mentioning
confidence: 99%